(untitled) (Scientific journal of the Fergana State University, 2023)
The article helps to understand the history of Internet marketing terminology, its modern meaning, the emergence and development of the concept of marketing. In addition, the essence of the concept of a term in linguistics, its morphological structure and differences from other lexical units are considered. It also presents the information about the problems of standardization of terms that are borrowed into the Uzbek language.